DCAF13 promotes breast cancer cell proliferation by ubiquitin inhibiting PERP expression. Issue 5 (18th March 2022) - Shan, Bao‐Qian; Wang, Xiao‐Min; Zheng, Li; Han, Yao; Gao, Jie; Lv, Meng‐Dan; Zhang, Yi; Liu, Yi‐Xuan; Zhang, Han; Chen, Hao‐Sa; Ao, Lei; Zhang, Yin‐Li; et al.
Abstract: Evolutionarily conserved DDB1‐and CUL4‐associated factor 13 (DCAF13) is a recently discovered substrate receptor for the cullin RING‐finger ubiquitin ligase 4 (CRL4) E3 ubiquitin ligase that regulates cell cycle progression. DCAF13 is overexpressed in many cancers, although its role in breast cancer is currently elusive. In this study we demonstrate that DCAF13 is overexpressed in human breast cancer and that its overexpression closely correlates with poor prognosis, suggesting that DCAF13 may serve as a diagnostic marker and therapeutic target. We knocked down DCAF13 in breast cancer cell lines using CRISPR/Cas9 and found that DCAF13 deletion markedly reduced breast cancer cell proliferation, clone formation, and migration both in vitro and in vivo . In addition, DCAF13 deletion promoted breast cancer cell apoptosis and senescence, and induced cell cycle arrest in the G1/S phase. Genome‐wide RNAseq analysis and western blotting revealed that loss of DCAF13 resulted in both mRNA and protein accumulation of p53 apoptosis effector related to PMP22 (PERP). Knockdown of PERP partially reversed the hampered cell proliferation induced by DCAF13 knockdown. Co‐immunoprecipitation assays revealed that DCAF13 and DNA damage‐binding protein 1 (DDB1) directly interact with PERP. Overexpression of DDB1 significantly increased PERP polyubiquitination, suggesting that CRL4 DCAF13 E3 ligase targets PERP for ubiquitination and proteasomal degradation. In conclusion, DCAF13 and the downstream effector PERP occupy key roles in breast cancer proliferation and potentially serve as prognostics and therapeutic targets. Abstract : DCAF13 is overexpressed in breast cancer and its overexpression closely correlates with the poor prognosis. DCAF13 deletion markedly decreased breast cancer cell proliferation, clone formation, and migration both in vitro and in vivo.DCAF13 promotes breast cancer cell proliferation by inhibiting the expression of PERP.